(untitled) - Boza, Sofía; Muñoz, Tomás; Rico, Margarita; Muñoz, Jazmín (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Development programs for female farmers : identifying clusters for the case of Chile s "Education and training program for rural women (2018)
This article aims to contribute to the evaluation of development policies for female farmers based on their beneficiaries attitudes. For this, it was conducted a survey in the Metropolitan Region of Santiago, Chile, to a representative sample of participants in the "Education and training program for rural women" of the Chilean National Institute for Agricultural Development. The questionnaire applied was divided into the following sections: i) personal characteristics of the farmers and their family unit; ii) technical, productive and commercial features; iii) farm and household income; and iv) vision of themselves and program-related attitudes. The data collected was processed by descriptive and multivariate techniques such as principal components and cluster analysis. The results show a positive assessment of the program on an aggregate level, although there are significant dissimilarities within the sample, allowing three clusters to be identified: "reticent participants" (42.3%), "associative participants" (20.5%) and "empowered participants" (37.2%). The farmers on those clusters present differences not only in their attitudes towards the program but also in their education level, income, farm profitability and balance between productive and domestic roles. Its concluded that individual characteristics and circumstances impact beneficiaries perception of the programs, which should be considered in their design and implementation.